Answer:
1889.02
Step-by-step explanation:
Step-by-step explanation:
y = 9x - 7
When x = 8
y = 9.8 - 7
y = 72 - 7
y = 65
When x = 6
y = 9.6 - 7
y = 54 - 7
y = 47
When x = 7
y = 9.7 - 7
y = 63 - 7
y = 56
When x = -8
y = 9.(-8) - 7
y = -72 - 7
y = -79
When x = 4
y = 9.4 - 7
y = 36 - 7
y = 29
In an arithmetic series, the value of the nth term is calculated using the equation,
an = ao + (n - 1)(d)
where an and ao are the nth and the 1st term, respectively. d is the common difference, and n is the number of terms.
In the given, an = 48, a0 = 93, d = -5 and n is unknown. Substituting the known values,
48 = 93 + (n - 1)(-5)
The value of n from the equation is 10. Thus, the answer is the last choice.
Answer
n <u>< </u>14
Step-by-step explanation:
simplify 2n<28
2n/2<28/2
simplify n<14